Functional Characterization of Alanine Racemase from Schizosaccharomyces pombe: a Eucaryotic Counterpart to Bacterial Alanine Racemase - Uo, Takuma (American Society for Microbiology, 2001)
Schizosaccharomyces pombe has an open reading frame, which we named alr1(+), encoding a putative protein similar to bacterial alanine racemase. We cloned the alr1(+) gene in Escherichia coli and purified the gene product (Alr1p), with an M(r) of 41,590, to homogeneity. Alr1p contains pyridoxal 5′-phosphate as a coenzyme and catalyzes the racemization of alanine with apparent K(m) and V(max) values as follows: for l-alanine, 5.0 mM and 670 μmol/min/mg, respectively, and for d-alanine, 2.4 mM and 350 μmol/min/mg, respectively. The enzyme is almost specific to alanine, but l-serine and l-2-aminobutyrate are racemized slowly at rates 3.7 and 0.37% of that of l-alanine, respectively. S. pombe uses d-alanine as a sole nitrogen source, but deletion of the alr1(+) gene resulted in retarded growth on the same medium. This indicates that S. pombe has catabolic pathways for both enantiomers of alanine and that the pathway for l-alanine coupled with racemization plays a major role in the catabolism of d-alanine. Saccharomyces cerevisiae differs markedly from S. pombe: S. cerevisiae uses l-alanine but not d-alanine as a sole nitrogen source. Moreover, d-alanine is toxic to S. cerevisiae. However, heterologous expression of the alr1(+) gene enabled S. cerevisiae to grow efficiently on d-alanine as a sole nitrogen source. The recombinant yeast was relieved from the toxicity of d-alanine.